In vitro Evaluation of Mannosylated Paromomycin-Loaded Solid Lipid Nanoparticles on Acute Toxoplasmosis - Khosravi, Mojdeh; Mohammad Rahimi, Hanieh; Doroud, Delaram; Mirsamadi, Elnaz Sadat; Mirjalali, Hamed; Zali, Mohammad Reza (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii is a zoonotic intracellular protozoan with worldwide distribution. Acute and sever toxoplasmosis are commonly reported from patients who suffer from acquired/congenital immune deficiency. This study aimed to synthesize mannosylated paromomycin-loaded solid lipid nanoparticles (PM-SLN-M) and evaluate it on acute toxoplasmosis. SLN was synthesized and then was loaded by 7 mg/mL paromomycin sodium. Mannose coating was performed and after washing, the size, zeta potential, and loading percentage were calculated. To evaluate the cell toxicity, MTT assay was performed on Vero cells by different concentrations (log 10-1) of SLN, PM-SLN-M and PM-SLN. As well, the anti-Toxoplasma effects were also evaluated using trypan-blue staining and scanning electron microscopy. MTT assay was also employed to evaluate the effects of PM and PM-SLN-M on intracellular Toxoplasma. Six-month stability test of PM-SLN and PM-SLN-M represented that characteristics were all remained constant. The cell viability assay demonstrated that PM-SLN-M had lower cell toxicity (<20%) compared to PM-SLN (<30%) and PM (<40%). Statistical analysis showed that PM-SLN-M significantly killed 97.555 ±0.629 (95% CI: 91.901 to 103.209) (P<0.05) of T. gondii tachyzoites. More than 50% of Toxoplasma-infected Vero cells remained viable in concentrations more than 0.07 µg/mL and 7 µg/mL of PM and PM-SLN-M, respectively. SEM analysis showed that T. gondii tachyzoites were changed in both size and morphology facing with PM-SLN-M. Our findings indicated that synthesized PM-SLN-M had anti-Toxoplasma activity without significant host cell toxicity at the highest concentration. Our study demonstrated that PM was able to kill intracellular Toxoplasma in lower concentration in comparison to PM-SLN-M, although PM-SLN-M showed lower cytotoxic effects on Vero cells.